2022
DOI: 10.1002/ejoc.202200684
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Benzothiazinones from Benzoyl Thiocarbamates: Application to Clinical Candidates for Tuberculosis Treatment

Abstract: Benzothiazinones are a structural motif found in biologically active compounds, such as the clinical candidates BTZ-043 and Macozinone for the treatment of tuberculosis. We describe a robust, two-step method to synthesize 2-amino-substituted benzothiazinones from benzoyl thiocarbamates, which were prepared in a one-pot procedure from benzoyl chlorides. The intramolecular cyclization and ethoxy displacement steps were also amenable to adoption in continuous flow as exemplified by select substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…7). 52 Reaction with ammonium isothiocyanate gives benzoyl isothiocyanates 15 , which are reacted in situ with ethanol to obtain stable benzoyl thiocarbamates 16 . Intramolecular cyclization in the presence of DBU as a base then yields 2-ethoxy-BTZs 17 .…”
Section: Synthesismentioning
confidence: 99%
See 2 more Smart Citations
“…7). 52 Reaction with ammonium isothiocyanate gives benzoyl isothiocyanates 15 , which are reacted in situ with ethanol to obtain stable benzoyl thiocarbamates 16 . Intramolecular cyclization in the presence of DBU as a base then yields 2-ethoxy-BTZs 17 .…”
Section: Synthesismentioning
confidence: 99%
“…41 Connor et al reported isolated yields up to 75% for the 2-ethoxy replacement step using piperidine, as a model secondary amine substrate, under optimized microwave conditions. 52…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation